Filozoficzno-etyczne rozwinięcie idei społecznej odpowiedzialności biznesu - Kaczocha, Włodzimierz (Philosophical and Ethical Development of the Idea of Social Responsibility of Business, 2009)
The author explains and develops A. Carnegie's idea of social responsibility and he studies some modern concepts (D.J. Den Uyl, W.M. Evan, R.E. Freeman). The author also presents some critical viewpoints by M. Friedman and O. J Bocheński. The paper justifies the opinion that business social responsibility might be understood as Kant's "idea of practical thought". The author puts forward his own opinion saying that business social responsibility should be perceived as (1) voluntary charity performed by entrepreneurs and managers, and (2) an ethically grounded and legally recognized general duty. Such responsibility is acceptable, once the idea of shared justice has been considered and recognized.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 26-37